DNA vaccines expressing a fusion product of outer surface proteins A and C from Borrelia burgdorferi induce protective antibodies suitable for prophylaxis but Not for resolution of Lyme disease - Wallich, Reinhard; Siebers, A.; Jahraus, Oliver; Brenner, Christiane; Stehle, T.; Simon, M.M. (Infection and immunity, 2001)
DNA vaccines encoding the outer surface protein A (OspA) of Borrelia burgdorferi have been shown to induce protective humoral responses capable of preventing but not curing infection in mice. Subsequent studies showed that an established infection or disease could be resolved by passive transfer of antibodies to OspC. In the present study, DNA vaccines encoding either the OspC antigen alone or fused to OspA and under the transcriptional control of the human elongation factor 1alpha promoter were evaluated for their protective and/or curative potential. In contrast to ospA-containing plasmids, none of the six constructs with ospC alone were immunogenic in vivo, independent of whether they contained promoter or leader sequences from ospA and/or ospC, or alternatively, the signal sequence of the human tissue plasminogen activator. Solely, a DNA vaccine encoding an OspA-OspC fusion product led to expression of the respective polypeptide chain in transfected cells in vitro and to the induction of OspA- and OspC-specific antibodies in vivo. Immune sera raised against the OspA-OspC fusion product conveyed full protection against subsequent infection, most probably via OspA-specific antibodies, but were unable to resolve infection.
Gesehen am 26.02.2021